EXPERIMENTAL DETERMINATION OF TRACE ELEMENT PARTITION COEFFICIENTS IN CULTURED BENTHIC FORAMINIFERA - Havach S.M.; Chandler G.T.; Wilson-Finelli A.; Shaw T.J. (My University, 2001)
We present the first trace metal partition coefficients obtained from reproducing cultures of deep-sea benthic foraminifera. Paleoceanographically important species, including juvenile Bulimina marginata, Cibicidoides pachyderma, and Uvigerina peregrina, were maintained in sediment microcosms at 10°C, 35 psu, and pH 8 for 1-3 years. Juvenile foraminifera were separated, cleaned, and dissolved under clean conditions for determination of trace metal partition coefficients on recently deposited (1-3 months) foraminiferal calcite. In addition to the deep-sea species, we analyzed a shallow water benthic foraminifer, Ammonia beccarii. Overlying water samples were collected from the microcosms concurrent to the period of calcification (3 months prior to separation). Ba/Ca partition coefficients (DBa) were measured in replicate for benthic foraminifera species Bulimina marginata (0.24 +/- 0.07), Uvigerina peregrina (0.24 +/- 0.06, Ammonia beccarii (0.20 +/- 0.04). The DBa for Bulimina marginata and Uvigerina peregrina were found to closely match the range from the Ontong Java Plateau. Sample size limitations allowed for only one analysis of DBa for Cibicidoides pachyderma. However, our nonreplicated DBa of 0.5 +/- 0.1 falls within the accepted range of core top samples (0.37 +/- 0.06). We report a DCd for Ammonia of 1.0 +/- 0.5, for Cibicidoides of 4 +/- 2, for Bulimina of 3 +/- 1, and for Uvigerina 2 +/- 1 which all fall within the ranges reported for core top calibrations. The large uncertainties in DCd reflect variation in dissolved Cd concentration in the artificial seawater reservoir due to loss and replacement of Cd during the course of the experiment. The variability between species is probably the result of variability in pore water Cd in the sediment culture system and may reflect habitat effects.